El señor absoluto como superación de la inmediatez en la Fenomenología del espíritu - Mansilla, Katherine (2016)
This article analyses the Hegelian notion of death, presented in the Phenomenology of Spirit. In this work, Hegel names death the “absolute master” and this idea appears in two different sections of the text. The first mention of the absolute master is in the death struggle for recognition (self-consciousness), whereby the slave, who is aware of death and due to it experiments the anguish of its arrival, abandons the struggle to live at the service of his master. Thus, overcoming his own fear of death, the slave finds in its expression the transformation of the world. The second mention takes place in the analysis of the terror lived during the French Revolution. In this part, Hegel describes how the abstraction of absolute freedom is imposed upon all citizens, generating death and terror among individuals. In both experiences that the subjects (the slave and the citizens) respectively face, death appears as an experience that opens us to reflection and allows us to overcome immediacy.